Justice and Agreement in Islamic Inheritance Distribution: An Analysis of Religious Court Decisions in Indonesia - Panji Nugraha Ruhiat; Ah. Fathonih; Siah Khosyi’ah; Syamsuddin RS; Nadia Safira Firdaus (Universitas Muhammadiyah Bandung, 2025)
This research departs from the debate on the tension between normative inheritance division (faraidh) and the demands of substantive justice in contemporary Muslim family dynamics. The main problem of this research is how the principle of justice is manifested in the distribution of inheritance based on mutual agreement (ash-shulhu) and how it is implemented in the practice of religious justice. This study uses normative-empirical legal methods with legislative, conceptual, and case study approaches to practices in the Religious Court. The findings of the study show that the principle of justice in inheritance agreements is built on the principles of voluntariness, willingness, equality of rights, and benefits, which are substantively in line with the values in the Compilation of Islamic Law (KHI). In practice, the implementation of inheritance agreements is carried out through mediation mechanisms in contentious cases or through reinforcement by judges in the form of decisions or determinations, as long as it does not violate sharia principles and the absolute rights of heirs. This approach has proven effective in preventing protracted conflict and creating more contextual justice. This study contributes to the debate on the reconciliation between normative Islamic inheritance law and considerations of sociological justice in contemporary Muslim society. Theoretically, this study emphasizes that the concept of justice in Islamic inheritance law is not rigid, but adaptive through an agreement mechanism that remains in the sharia corridor. The recommendation of this study is the need to strengthen the role of mediation and more explicit judicial guidelines in accommodating substantive justice-based inheritance agreements in the religious justice environment.